Record of the largest longtail tuna, Thunnus tonggol (Bleeker 1851) from off shore Salalah in the Sultanate of Oman - Al-Mamari, Dawood; Al-Kharusi, Lubna; Al-Kiyumi, Fatma; Al-Shogebai, Saeed; Al-Anboori, Ibrahim; Al-Seneadi, Rashed; Khrorv, Sergiy (Journal of Fisheries, 2014)
Capture of a great Longtail tuna, Thunnus tonggol from off Shore of the city of Salalah, Arabian Sea, Sultanate of Oman in January 2013 is described in this paper. Its morphometric and meristic characters are discussed.